The relationship between reactive agility and change of direction speed in professional female basketball and handball players - Popowczak, M.; Cichy, I.; Rokita, A.; Domaradzki, J. (Frontiers in Psychology, 2021)
Assessing the physical ability of players to perform change of direction and the cognitive and motor abilities revealed in reactive agility (RA) is necessary to understand the physical requirements and capabilities of professional players in handball and basketball. The main aim of this study was to determine the differences between professional female basketball and handball players in terms of anthropometric features, change of direction speed (CODS), and the RA task. Moreover, the relationships among anthropometric features, agility, and parameters of perception were determined. Two scenarios of the Five-Time Shuttle Run to Gates test (planned and unplanned) were used to evaluate the CODS and RA. The response time (RT) was also measured in the unplanned scenario. Additionally, the index of reactivity (REAC-INDEX) was specified as the difference between the RA test result and the measurement of CODS. There was a significant difference found in terms of body height, with basketball players being taller than handball players (p = 0.032). Professional female handball players achieved better results than professional female basketball players with regard to RA tasks (p = 0.01) and CODS (p = 0.041). Significant simple correlations between each anthropometric feature (body height, body mass) and values for CODS and RA were observed (r = 0.49-0.53). Applying partial correlation allowed for the assessment of actual relationships among CODS, RA, RT, and REAC-INDEX, without a confounding variable. Detaching the anthropometric parameters from the rest of the relationships resulted in maintenance or changes in r-values and an increased significance in the relationships between each pair: RA vs. RT, RA vs. REAC-INDEX, and RT vs. REAC-INDEX. The strongest associations were related to RT vs. REAC-INDEX (r = 0.97 at detaching body height or body mass, p < 0.001) and CODS vs. RA (r = 0.66 at detaching body height and r = -0.67 at detaching body mass, p < 0.001). It is recommended to use partial correlations in subsequent studies, as simple correlations are not reliable and may not reveal the apparent relationships between the variables. In addition, when determining the CODS and RA, it is suggested to take anthropometric and perception variables into account, such as reaction time or REAC-INDEX.